Radiation exposure during cardiac device implantation: Lessons learned from a multicenter registry. Issue 1 (11th December 2019) - Bru, Paul; Dompnier, Antoine; Amara, Walid; Haddad, Georges; Galuscan, Gianina; Sagnol, Pascal; Steinbach, Mathieu; Montagnier, Christian; Taieb, Jérôme; Beguec, Julien; Milhem, Antoine; ,
Abstract: Background: Little data are available about radiation exposure during cardiac electrical device implantation, and no dose reference levels have been published. This multicenter, prospective, observational study assesses patient and staff radiation exposure during cardiac device implantations, and aims at defining dose reference levels. Methods: Patient demographic, procedural, and radiation data were obtained for 657 procedures from nine institutions. Physician and staff exposure were measured using real‐time dosimeters worn beneath and above lead apron. Statistical analysis included fluoroscopy time (FT), dose‐area product (DAP), and DAP adjusted for FT and body mass index. Results: Pacemakers and cardioverter defibrillators were implanted in 481 and 176 patients, respectively. Of these, 152 were treated with cardiac resynchronization therapy (CRT). Median FTs were 837s (interquartile range [IQR]: 480‐1323), 117s (IQR: 69‐209), and 101s (IQR: 58‐162), and median DAPs were 1410 (IQR: 807‐2601), 150 (IQR: 72‐338), and 129 (IQR: 72‐332) cGy.cm² for biventricular, dual chamber, and ventricular device implantation, respectively. Dose reference levels correspond to the third quartile values. During CRT, higher exposure was observed with four X‐ray systems than with the two newer and customizable ones (adjusted DAP of 0.90 [IQR: 0.26‐1.01] and 0.29 [IQR: 0.23‐0.39], respectively; P  < .001). Conclusion: Based on real‐life measurements, this multicenter registry provides dose reference levels and may help centers assess radiation exposure. Although biventricular device implantation was responsible for the highest radiation exposure, FT was meaningfully shortened compared to previously reported values. For a same FT, the use of new generators and custom settings has significantly reduced DAP.